EFEKTIVITAS PENCAIRAN DANA, PEMBAYARAN GAJI PEGAWAI - Nengsih, Fitria; Heriyanto, Meyzi; Farida, Lena (Jurnal Ilmu Administrasi Negara, 2018)
Effectiveness of Fund Management, Employee Salary Payment. The purpose of this study is to analyze the effectiveness of the management of funds, especially salaries made by the Department of Education and Culture of Meranti Regency. Research conducted in the District of Meranti Islands with research subjects are treasurer Department of Education and Culture and Treasurer UPTD Kepualauan District Meranti. This research use desciptive qualitative approach. Instruments used to collect data using interview techniques, observation and documentation. Based on the results of the research can be seen that the treasurer salary and treasurer UPTD in the payroll employee salaries provide a good impact and a real change for employees Education and culture district meranti archipelago.